Pediatric Integrated Care Models: A Systematic Review. (February 2020) - Burkhart, Kimberly; Asogwa, Kenneth; Muzaffar, Nida; Gabriel, Mary
Psychiatric disorders are becoming more frequently diagnosed within the pediatric primary care setting. Despite increased diagnosis within primary care, only a minority of patients receive further psychiatric or specialty care. The integrated/collaborative care treatment model was designed to improve access within primary care. The purpose of this review is to identify randomized controlled trials and quasi-experimental studies that have investigated whether increased access improves treatment engagement, satisfaction, and improved mental health outcomes. Six studies met inclusion criteria. Studies reviewed indicated increased access to behavioral health treatment through use of the integrated/collaborative care model and improved mental health outcomes. Recommendations for screening and treatment are provided. Limitations of the reviewed studies include lack of generalizability to urban populations, minority youth, and youth younger than 4 years of age. Practice recommendations to address these limitations are identified.